Nutritional management in Incremental Hemodialysis Patients - Banjongjit, Athiphat; Kittiskulnam, Piyawan (Journal of the Nephrology Society of Thailand, 2022)
In many countries including Thailand, thrice-weekly hemodialysis has been routinely prescribed in end stage kidney disease patients initiating hemodialysis regardless of their residual kidney function. This prescription was based on randomized controlled trials assessing urea clearance in patients who had little or no residual kidney function. However, some incident hemodialysis patients still have significant residual kidney function which will decline rapidly after thrice-weekly hemodialysis. This might lead to long-term unfavorable outcomes including increased mortality. From the current evidence, measures to preserve the residual kidney function include regular monitoring of the residual kidney function, avoidance or minimizing nephrotoxic agents, blood pressure control, avoidance of intradialytic hypotension, using of high-flux biocompatible dialyzer, and using ultrapure dialysate. Less frequent hemodialysis is also considered as a possible measure and there is an emerging concept of incremental hemodialysis, that is to start hemodialysis with less frequent manner in patients with adequate residual kidney function, and to increase hemodialysis frequency when the residual kidney function decline to the point of inadequate solute clearance. This dialysis regimen should be applied along with the limitation of dietary protein intake to reduce uremic toxin generation as well as the restriction of dietary sodium and fluid to reduce interdialytic weight gain. According to the current evidence, patients who initiate once-weekly dialysis should limit their dietary protein intake to 0.6 grams per kilogram of body weight per day in non-dialysis day and liberate their protein intake in the dialysis day. For those receiving twice-weekly or thrice-weekly hemodialysis, dietary protein intake should be 1.0-1.2 grams per kilogram of body weight per day for both dialysis and non-dialysis days.